Note on \((i,j)\)-Distance Graph of a Graph - Hemavathi, P. S.; Lokesha, V. (Communications in Mathematics and Applications, 2018)
In this note, we dene the \((i,j)\)-distance graph of a graph and presented several characterizations based on this notion.